Aqueous two-phase systems strategies to establish novel bioprocesses for stem cells recovery. (December 2014) - González-González, Mirna; Rito-Palomares, Marco
Abstract During the past decade, stem cell transplantation has emerged as a novel therapeutic alternative for several diseases. Nevertheless, numerous challenges regarding the recovery and purification steps must be addressed to supply the number of cells required and in the degree of purity needed for clinical treatments. Currently, there is a wide range of methodologies available for stem cells isolation. Nevertheless, there is not a golden standard method that accomplishes all requirements. A desirable recovery method for stem cells has to guarantee high purity and should be sensitive, rapid, quantitative, scalable, non- or minimally invasive to preserve viability and differentiation capacity of the purified cells. In this context, aqueous two-phase systems (ATPS) represent a promising alternative to fulfill the mentioned requirements, promoting the use of stem cell-based therapies for incurable diseases. This practical review focuses on presenting the bases for the development of a novel and scalable bioprocess for the purification of stem cells, with a case scenario of CD133+ cells. The bioengineering strategies include the application of immunoaffinity ATPS in its multiple variants, including antibody-polymer conjugation, antibody addition and antibody immobilization. Conclusions are drawn in the light of the potential generic implementation of these strategies as an initial step in the establishment of bioprocesses for the purification of stem cells.